The effectiveness of a single session of mindfulness-based cognitive training on cardiac vagal control and core symptoms in children and adolescents with attention-deficit/hyperactivity disorder (ADHD): a preliminary randomized controlled trial. - Robe, Andreea; Dobrean, Anca (European Child & Adolescent Psychiatry, 2023)
This study examined the effectiveness of a mindfulness-based intervention (MBI) on Conners' continuous performance test scores (CPTs), cardiac vagal control (CVC) assessed by vagally mediated heart rate variability (HRV), and mood in children and adolescents with ADHD. We conducted a randomized controlled trial (RCT) recruiting 70 children and adolescents (M age 11.03, SD 2.78) with a clinical diagnosis of ADHD, which were allocated to either 1 session of mindfulness cognitive training, or an active control condition and were examined at baseline, post-treatment and 4-week follow-up. See clinicaltrials.gov: NCT04316832. There was a significant main effect of time on the primary outcomes measured by CPT scores of attention-related problems (omission errors, reaction time) and hyperactivity–impulsivity (commission errors). However, time-by-group interaction did not achieve statistical significance for commission errors and hit RT, indicating that the changes over time in these outcomes were not significantly different between the MBI and Control conditions. In addition, there was a significant time-by-group interaction for omission errors. Relative to control, MBI resulted in a small (d = 0.011) non-statistically significant reduction in omission errors post-treatment. Furthermore, there were no significant differences in detectability. Secondary outcomes were CVC and mood. A small treatment effect on CVC (d = 0.37) was observed; there was a slight increase in vagally mediated HRV measure post-treatment. There were no significant differences in mood improvement over time between conditions. One brief session of MBI effectively enhances CVC but does not significantly improve CPT scores of attention-related problems and hyperactivity–impulsivity or mood in children with ADHD. Clinicaltrials.gov: NCT04316832.